2016
DOI: 10.1111/nmo.13009
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and waist reduction is associated with improvement in gastroesophageal disease reflux symptoms: A longitudinal study of 15 295 subjects undergoing health checkups

Abstract: Weight loss or waist reduction was associated with improvement in GERD symptoms only in subjects with general or abdominal obesity. Weight loss or waist reduction will be an important treatment option in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
2
24
1
2
Order By: Relevance
“…Compared with the NF group, body weight was significantly reduced in the IFR group from the 38th to 50th week of life (p \ 0.05), with around 19.2 and 22.5% loss of the body weight (Fig. 2a), respectively, consistent with the previous reports in mammalian species, including humans (Harvie et al 2011;Jeong et al 2016;Manzanero et al 2014;Park et al 2016). However, body length of the fishes in the groups showed little difference during the periods (Fig.…”
Section: Ifr Causes Body Weight Losssupporting
confidence: 91%
“…Compared with the NF group, body weight was significantly reduced in the IFR group from the 38th to 50th week of life (p \ 0.05), with around 19.2 and 22.5% loss of the body weight (Fig. 2a), respectively, consistent with the previous reports in mammalian species, including humans (Harvie et al 2011;Jeong et al 2016;Manzanero et al 2014;Park et al 2016). However, body length of the fishes in the groups showed little difference during the periods (Fig.…”
Section: Ifr Causes Body Weight Losssupporting
confidence: 91%
“…21 Another large retrospective study, with more than 15,000 patients, showed an association between improvement in GERD symptoms and reduction in body mass index (BMI) in obese patients who lost at least 2 kg/m 2 in BMI (odds ratio 2.34). 22 Diet, smoking cessation, alcohol moderation. Numerous studies have aimed to fi nd foods that exacerbate refl ux symptoms.…”
Section: Lifestyle Modifi Cationsmentioning
confidence: 99%
“…[5][6][7] Although many studies have investigated the association between obesity and GERD, these studies have been cross-sectional or case-control studies or meta-analyses of cross-sectional or case-control studies. [5][6][7][8] Recently, follow-up studies evaluated the relationship between weight change and GERD, [9][10][11][12][13][14][15][16] and some of them used endoscopy for GERD. [12][13][14][15][16] Erosive esophagitis (EE) is a complication of GERD that can be easily detected via endoscopy and used as an objective criterion for the diagnosis of GERD.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Recently, follow-up studies evaluated the relationship between weight change and GERD, [9][10][11][12][13][14][15][16] and some of them used endoscopy for GERD. [12][13][14][15][16] Erosive esophagitis (EE) is a complication of GERD that can be easily detected via endoscopy and used as an objective criterion for the diagnosis of GERD. 1) However, studies exploring the development of EE stratified by weight change are rare.…”
Section: Introductionmentioning
confidence: 99%